The mystery of the hidden beach - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (New York, NY : Scholastic, 1994)
While visiting the Florida Keys, the Aldens encounter suspicious characters, strange incidents at night, and a plot to steal valuable coral.
Keywords: Coral reefs and islands -- Fiction; Florida Keys (Fla.) -- Fiction; Mystery fiction